REFLEKSI PENCIPTAAN TARI NYI PANDANARAN PRAJURIT PEREMPUAN - Anjali, Sangghita; Soemaryatmi, Soemaryatmi (Institut Seni Indonesia Surakarta, 2022)
The Nyi Pandanaran Prajurit Perempuan dance is a choreography created by Sangghita Anjali in 2021. This dance will be performed at the ISI Surakarta Great Theater building on January 7, 2022. The Nyi Pandanaran Prajurit Perempuan dance has a theme of soldiering. This work is presented by a single female dancer. The title of this research is Reflection on the Creation of the Female Warrior Nyi Pandanaran Dance which will reveal two problems, namely how the creative process of the female warrior Nyi Pandanaran dance is and how the form of the dish is presented. To dissect the Creative Process problem, Mel Rodhes's theory of 4P (Four P’s Creativity) Thoughts is quoted by Utami Munandar, while the Form of Serving uses the theory of Forms according to Djelantik. This study uses an artistic practice-based research method consisting of Re-Visiting/visiting again, Re-Questioning/questioning, and Re-Interpreting/re- interpreting. The results of this study indicate that the Creative Process of compiling the Nyi Pandanaran Prajurit Perempuan dance was produced through the stages of preparation, incubation, illumination, and leveraging/evaluation. Nyi Pandanaran Dance Prajurit Perempuan is a dance that is presented in a singular form. The dance moves used are traditional movements with clothing designs inspired by the Semarang model warriors, and using gamelan musical instruments combined with modern musical instruments such as the saxophone and chimes. These elements are assembled into one in a presentation, in a plot consisting of three scenes that reveal an atmosphere of majesty, firmness, determination, persistence, and submission. The Nyi Pandanaran Prajurit Perempuan dance is a choreographic creativity that is packaged in totality.